Comparative Study on the Management and Utilization of Takimpo Sara Land Based on Customary Law in Indonesia and Nigeria - Salam, Safrin; Slamet, Agus; Mahmuda, Dewi; Miqat, Nurul; Izu, Cynthia C. (Media Iuris, 2025)
This study analyzes the management and utilization of Sara customary land in Takimpo Village, Buton Regency, managed by the indigenous community based on customary law principles, and compares it with the customary land management system in Nigeria. Sara land holds significant cultural, social, and economic value for the indigenous community, who manage it based on principles of collectivity and consensus. The research method used is socio-legal, employing a qualitative approach through interviews, observations, and analysis of data obtained from the indigenous community, as well as relevant legal literature. The key findings indicate that the customary law principles in Takimpo emphasize communal land ownership, consensus as the decision-making mechanism, and sustainability in land use. Although customary law is respected, there is tension with state policies that prioritize individual land ownership. A comparison with Nigeria reveals similar principles of collectivity; however, state policies in Nigeria are more dominant, leading to tensions with the customary legal system. In conclusion, legal recognition of customary land needs to be strengthened in national land policies to protect the rights of indigenous communities. Mapping customary land based on customary law is essential to ensure sustainability and protect the rights of indigenous communities in managing their land.